THE RECEPTIVENESS OF THE TEUKU UMAR ISLAMIC LEADERSHIP STYLE AMONG INDONESIAN YOUNG LEADERS - Zainal Putra; Hanudin Amin; Hamdi Harmen; Said Achmad Kabiru Rafiie (Journal of Applied Structural Equation Modelling, 2025)
Drawing on the theory of planned behaviour (TPB), this paper investigates the factors that influence the behavioural intention of young Indonesian leaders to adopt the Teuku Umar Islamic leadership style. This study employed a purposive sampling technique to collect data from young Indonesian leaders. A total of 174 participants completed the questionnaire survey. The partial least squares structural equation modelling (PLS-SEM) approach was utilised to test the proposed hypotheses. All drivers drawn from the TPB were significantly related to the receptiveness of the Teuku Umar Islamic leadership style. Of the examined factors, perceived behavioural control exhibited the strongest influence, suggesting that leaders are more likely to adopt this leadership style when they perceive fewer obstacles in its implementation and organisational acceptance. By focusing on the key attributes of the TPB, policymakers and organisational leaders can enhance leadership development programmes, improve the applicability of the Teuku Umar Islamic leadership style and ensure its inclusion in a community-based leadership framework. This study provides a novel contribution by integrating an indigenous leadership model into the TPB framework–offering a contextual alternative to dominant Western-centric leadership theories.